Global significance of the microbiome according to the One Health approach : Review - Hancz, Csaba (Acta Agraria Kaposváriensis, 2021)
All-pervasive role and significance of microbiome is becoming more and more acknowledged thanks to the intense multidisciplinary research done in the last decades. Its global function and significance in the emerging, and the future fate of the biosphere is unequivocal and beyond dispute. Uncertainties and varied usage of synonyms justifies to define once again notions like microbiome, pro- and prebiotics and clarify their relations. Knowledge about microbes important for our health is expanding rapidly. Extensive research on pre- and probiotics leads to their rapid production and broadscale application in medicine, nutrition, and agriculture. Human, animal and environmental microbiome are results of co-evolution so adopting the holistic approach suggested by the One Health fighting zoonoses can be even more effective as well as global food production more environmental-friendly and sustainable.